Akad Qordhul Hasan Sebagai Strategi Baznas Jatim Dalam Mengoptimalisasikan Dana Zakat Untuk Pemberdayaan Ummat - Munir, Mohammad (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2018)
The formulation of the research problem in this thesis can be described as follows: First, How is the strategy of Baznas East Java in optimizing the zakat fund, second, How is the implementation of Qordhul Hasan in Baznas East Java, the third is the qordhul Hasan agreement in accordance with the fatwa Number: 19 / DSN-MUI / IV / 2001.             This qualitative research approach is research using explorative research method and descriptive research method. Data collection method is by interview with snowball technique, observation, documentation and literature study through several book and internet sources, hence the result of research finding of Baznas East Java in optimizing zakat fund there are five programs that is East Java Smart, East Java Healthy, East Java Devotion, East Java is prosperous and East Java cares. The empowerment of zakat makes the mustahik have the power of the development of resources of the community in the form of creativity, competence and thinking power considering the economic growth and technology so rapidly will greatly affect the ability of each individual in fulfilling the needs of his life then with prosperous Java Baznas program includes the aid of work tools, work in collaboration with BLK and Cooperation services provide the skills of UMKM and revolving capital assistance that partner with or work together with mosque board, Reading Qur’an community and county Baznas who know the condition of the mustahik by making a letter of application and ready to be surveyed to pilgrims who will get capital assistance. The procedure is that the aid will be handed over to the mosque administrator, reading Qur’an community and the county Baznas for the next of the same committee is handed over to mustahik who is well worthy of receiving assistance.        The result of the research showed that Eat Java Baznas is in accordance with the fatwa Number: 19 / DSN-MUI / IV / 2001 which reads "That one of the means of economic improvement that can be done by LKS / BAZNAS is channeling funds through Al-Qordh principle, to the customer or mustahik provided that the client / mustahik is obliged to return the funds received in accordance with the agreement. If the Client / Mustahik cannot refund part or all of his liability for his / her inability then may extend the repayment period or partially off or off his / her liabilities. Keywords: Qordhul Hasan Agreement, Strategy, Optimize, Zakat Empowerment